Analyzing the Influence of Online Advertisements on ISP Network Traffic - Redel, Renan Augusto; Zietz, Douglas; Uchikawa, Vitor; Pfitscher, Ricardo J. (Anais do Workshop de Gerência e Operação de Redes e Serviços (WGRS), 2024)
With the constant internet access increase and with a large offer of content, a priori free of charge, there has been a significant increase in data consumption on the network, and online advertising follows this trend. Online advertising allows advertisers to leverage their capital through its platform and allows the dissemination of products and services within the network. However, the advertises load, which, for the most part, is unwanted for users, impacts internet access plans contracted by customers. This work aims to measure the impact of such advertisements on network traffic. We rely on two network traces to characterize consumption patterns: one from a regional access ISP with 33 customers and 15 days of capture and one from a publicly available dataset with 2000 customers and 3 minutes of capture. The results show that at least 11% of all the traffic volume relates to advertising content on the regional ISP and 38% of the public dataset.